(untitled) (Jurnal Teknodik, 2021)
Salah satu tantangan bagi dunia pendidikan saat ini adalah bagaimana mengembangkan pendidikan karakter bagi siswa selama masa new normal. Kemendikbudristek menetapkan 6 indikator dari Profil Pelajar Pancasila. Guna mempermudah internalisasi Profil Pelajar Pancasila dalam pembelajaran baik oleh guru maupun siswa, dikembangkan Platform Merdeka Mengajar (PMM). Penelitian ini bertujuan untuk mengetahui penerapan pemanfaatan Platform Merdeka Mengajar dalam menginternalisasi nilai-nilai Pancasila. Sampel penelitian adalah guru-guru sekolah penggerak dan SMK Pusat Keunggulan yang telah mengikuti bimtek PMM tahun 2021. Pengumpulan data menggunakan kuesioner, observasi dan wawancara terbatas. Hasil penelitian menunjukkan bahwa: 1)Profil Pelajar Pancasila pada hakikatnya merupakan salah satu upaya internalisasi nilai-nilai Pancasila dalam pembelajaran, 2) PMM memiliki peran signifikan dalam penerapan Profil Pelajar Pancasila pada pembelajaran paradigma baru, dan 3) Internalisasi nilai-nilai Pancasila dalam penerapan Profil Pelajar Pancasila di masa new Normal berbantuan Platform Merdeka Mengajar dengan cara diterapkan dalam karakter keseharian yang dibangun dan dihidupkan dalam diri individu setiap pelajar melalui budaya sekolah, pembelajaran intrakurikuler, kokurikuler, maupun ekstrakurikuler di sekolah. Peningkatan pemanfaatan Platform Merdeka Mengajar dalam menginternalisasi nilai-nilai Pancasila melalui Profil Pelajar Pancasila, perlu didukung dengan upaya peningkatkan kualitas dan kuantitas konten Profil Pelajar Pancasila serta dukungan kebijakan dalam pemanfaatan PMM dan sinergi kolaborasi antara sekolah, pemerintah, masyarakat serta pemangku kepentingan. PMM dapat menjadi salah satu solusi dalam penguatan pembelajaran karakter melalui internalisasi nilai Pancasila bagi siswa generasi milenial, terutama pada saat pembelajaran tatap muka terbatas di masa new normal pandemi Covid-19. One of the challenges in education today is student character education during the new normal era. The Ministry of Education, Culture, Research, and Technology sets 6 indicators of the Pancasila Student Profile. To enhance the internalization of the Pancasila Student Profile in learning by both teachers and students, the Merdeka Mengajar Platform (MMP) is developed. The objective of this research is to know the implementation of MMP in internalizing the values of Pancasila. The sample is teachers of driving schools and Center of Excellence Vocational Schools who have participated in the PMM technical guidance in 2021. Data collection is through questionnaires, observation, and limited interviews. The result show that: 1) Pancasila Student Profile is essentially an effort to internalize Pancasila values in learning; 2) MMP has significant roles in the implementation of the Pancasila Student Profile in the new learning paradigm; and 3) The internalization of Pancasila values in the implementation of Pancasila Student Profile in the new normal era with MMP is applied in daily characteristics that are developed and enhanced in every student through school culture, intra-curricular, co-curricular, and extra-curricular learning at school by applying it to the daily character that is built and brought to life in each student through school culture, intra-curricular, co-curricular, and extra-curricular learning at school. The improvement of MMP implementation in internalizing Pancasila values through Pancasila Student Profile should be supported by increasing the quality as well as quantity of Pancasila Student Profile contents, by policies in MMP implementation, and collaboration between schools, government, and other stakeholders. MMP can be one of the solutions to enhance character education through the internalization of Pancasila values for millennial students, especially during the limited face-to-face learning in a new normal era of pandemic covid-19